Infection of female squirrel monkeys (Saimiri sciureus) with trichomonas vaginalis as a model of trichomoniasis in women. - Street, D A (1983)
Marmosets, tamarins, owl monkeys, and squirrel monkeys were inoculated intravaginally with Trichomonas vaginalis. The latter animal species was most susceptible, trichomonads being recovered from four of six monkeys for periods ranging usually up to one month. Vaginal discharge was seen in most infected animals but polymorphonuclear leucocytes were rare. Infected animals developed serum IgG antibody responses and also local IgG and IgA responses, the latter occurring sometimes on reinoculation in the absence of organism recovery. Antibody responses were, however, of short duration and, overall, immunity was weak because two animals were reinfected on a second or subsequent challenge. Some of the observations are relevant to vaginal trichomoniasis in women.